Analisis Ketergantungan Masyarakat Terhadap Hasil Hutan Bukan Kayu Pada Taman Nasional Lore Lindu (Studi Kasus Desa Sidondo I Kecamatan Biromaru dan Desa Pakuli Kecamatan Gumbasa) - Abraham Neil; Golar Golar; Hamzari Hamzari (Universitas Tadulako, 2016)
People living around the forest area depend on forest and forestry activities. Dependence might be seen from economic, social and cultural aspects. This was descriptive research using survey approach. The respondents were sampled from the population who live as subvillage 5, Sidondo I and subvillage 2, Pakuli around LLNP by using questionnaires. The results showed the utilization forms of non timber forest products are bamboo used for building materials, firewood for energy sources and candlenut for food sources. Bamboo and candlenut are non timber forest products that might be income sources, firewood is for everyday purposes. All the three forest products are non timber forest products are predominantly conection by respondents from LLNP area. The people’s dependence upon the LLNP from economic aspect is quite high, while the social aspect and the cultural aspect is low.